2017
DOI: 10.1016/j.coph.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Modulating bile acid pathways and TGR5 receptors for treating liver and GI diseases

Abstract: Bile acids are central signals in enterohepatic communication and also integrate microbiota-derived signals into this signaling axis. Discovery of the tissue distribution and signaling pathways activated by the natural receptors for bile acids, farnesoid X receptor and G protein-coupled bile acid receptor 1 (GPBAR1) also known as TGR5, and bile acid transporters has led to the development of therapeutic agents that target these molecules. Obeticholic acid, a selective FXR agonist, and NGM282, a non-mitogenic F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…We began by investigating the effects of CBAs on canonical bile acid receptors farnesoid X receptor (FXR) and G protein-coupled bile acid receptor 1 (Takeda G protein-coupled receptor 5, TGR5) and their reported downstream mediators ( Figure 6A and refs. 30,31), which are increased by bile acid stimulation in various tissues (e.g., liver and kidney) (32,33). We found that lung transcript levels of Gpbar1 (TGR5) and downstream mediators Nos3 and Dio2, as well as transcript levels of Nr1h4 (FXR) and downstream mediators Abcb4, Abcc2, and Nr0b2, were not elevated in HDM plus TUDCA-treated mice compared with both the PBS and HDM control groups ( Figure 6B).…”
Section: Effects Of Other Cbas On Allergen-induced Inflammation and Tmentioning
confidence: 87%
“…We began by investigating the effects of CBAs on canonical bile acid receptors farnesoid X receptor (FXR) and G protein-coupled bile acid receptor 1 (Takeda G protein-coupled receptor 5, TGR5) and their reported downstream mediators ( Figure 6A and refs. 30,31), which are increased by bile acid stimulation in various tissues (e.g., liver and kidney) (32,33). We found that lung transcript levels of Gpbar1 (TGR5) and downstream mediators Nos3 and Dio2, as well as transcript levels of Nr1h4 (FXR) and downstream mediators Abcb4, Abcc2, and Nr0b2, were not elevated in HDM plus TUDCA-treated mice compared with both the PBS and HDM control groups ( Figure 6B).…”
Section: Effects Of Other Cbas On Allergen-induced Inflammation and Tmentioning
confidence: 87%
“…The liver is exposed to intestinal microbiota through the portal vein which delivers gut‐derived bacterial products or toxins, such as lipopolysaccharide and deoxycholic acid . The close structural and functional interaction between the gut and the liver is defined as the gut‐liver axis.…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…The liver is exposed to intestinal microbiota through the portal vein which delivers gut-derived bacterial products or toxins, such as lipopolysaccharide and deoxycholic acid. 6,92 The close structural and functional interaction between the gut and the liver is defined as the gut-liver axis. Liver diseases are often associated with intestinal dysbiosis, and it has been shown that gut bacterial metabolites could promote the development of chronic liver disease and HCC through gut-liver axis.…”
Section: Fmt For Digestive System Cancersmentioning
confidence: 99%
“…It not only inhibits bile acid formation from cholesterol by blocking CYP7a1 enzyme but also improves insulin sensitization and is believed to have favorable metabolic effects. 49 It has been studied in a recent phase IIa, randomized, placebo-controlled trial by enrolling 82 patients with biopsy-confirmed NASH (NAS ≥4 with one point in each component, fibrosis stage 1–3), with 8% liver fat content by MRI-PDFF and abnormal ALT. Subjects were randomized to 3 mg, 6 mg of NGM282, or placebo as a daily subcutaneous injection for 12 weeks.…”
Section: Introductionmentioning
confidence: 99%